Green finance and total factor energy efficiency: theoretical mechanisms and empirical tests - Yu, Shihai; Wang, Simin; Cheng, Xiaolan; Li, Lei (Frontiers in Environmental Science, 2024)
China’s green financial pilot policies (GFPPs) are an important start to build a green financial system in China. It is also an important part of achieving the “dual-carbon” goal. This paper calculates China’s total factor energy efficiency (TFEE), analyzes the impact of GFPPs on TFEE, and explores the conduction mechanism. The results show that the relationship between GFPPs and TFEE in the pilot areas is statistically significant. The GFPP mainly improves the TFEE through the green innovation effect and the optimization of the energy structure. The GFPP has a significant effect on TFEE enhancement in eastern coastal cities, non-old traditional industrial cities, and non-resource-based cities with high initial energy. China should continue to deepen the pilot work of green finance, formulate differentiated green finance policies, and ensure green technology innovation. This study provides empirical evidence for further optimization of green finance and energy efficiency.